Ground improvement using granular piles/piers case studies in the Philippines - Lafrades, Renanne SM.; Buensuceso, Benjamin Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Philippines is at its peak of industrialization; with the boom of constmctions of large scale facilities, the country's land mass is being maximized as much as possible. Therefore, even marginal or difficult sites are deemed feasible for the constmction of said structures. These large structures like Gas plants, factories, must be able to withstand a measurable amount of load for it to sustain its functionality let alone its stability. The use of Granular piles as soil improvement has been quite a trend. This main purpose of this study is to give comparative points between the different methods of installation of said technology. Extensive research, site and company visits were done to obtain information regarding these installations. Comparisons of theoretical on-site procedures and strengths were done as well as comparisons on the different methods. The mode of aggregate transfer, mode of compaction, and usage of water are the parameters used in comparison.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Foundations -- Philippines..; Columns -- Foundations; Piling (Civil engineering)